Investigation of Adjuncts Use in J. F. Kennedy’s Speech for the Members of Congress and Diplomatic Corps of Latin America on 13 March 1961 - Mercya Christ Sita Dewi (Ethical Lingua: Journal of Language Teaching and Literature, 2020)
This descriptive qualitative study investigates the types of adjuncts use in a spoken language grammar of J. F. Kennedy’s speech on 13 March 1961. Further, the study does examine the occurrence of each adjunct used in the recording. As it is described, adjuncts are an optional or structurally dispensable part of a sentence, clause, or phrase, when omitted, will not affect the remainder of the sentence being an element of clause structure with an adverbial function. In this current study, the researcher listed fourteen groups of adjuncts in the recording. The theory used to examine this study is stated in Carter & McCarthy’s (2006). The result conveys that the total numbers of adjuncts used in the speech are 75 adjuncts. In which adjuncts of place become the most frequent adjuncts in the speech. Next, focusing adjuncts be the most frequent number two with 14 total occurrences. The data show modal adjuncts could not be identified in the recording.